Pengembangan Media Pembelajaran Big Book Perjalanan Menuju Pancasila untuk Meningkatkan Pemahaman Sejarah Pancasila Siswa Kelas 3 Sekolah Dasar - Regina Sarudi; Susan Noviaty Herienth Jacobus (Journal on Education, 2024)
The Indonesian people will face many problems, one of which is a lack of understanding of the history of the birth of Pancasila. This research aims to develop Big Book learning media that is simple and easy for students to understand about the history of the birth of Pancasila. This research uses R&D (Research and Development). The development model applies 4 stages: 1) Define, 2) Design, 3) Develop, 4) Disseminate. The data collection techniques used are questionnaires, documentation and tests. Then, the data was analyzed through quantitative and qualitative data. As a result, 96.17% of material experts were described as "Very Appropriate" and the media expert validation percentage was 89.43% as "Very Appropriate". Practicality through a percentage of 98% is rated "Very Practical". The N-Gain effectiveness score was obtained at 0.76 or g>0.7 and the N-Gain amount was 76.01% rated as "Effective". In conclusion, the Big Book learning media that has been developed is considered feasible, effective and practical for use in Pancasila education learning content with material on the history of the birth of Pancasila for class III at SD GMIM 92 Bailang for the 2024/2025 academic year.